INFLUENCE OF PERCEPTION OF TERMS, PERCEPTION OF USEFULNESS AND RISK PERCEPTION ON DEBTOR DECISIONS WITH THERE IS A CREDIT RESTRUCTURING POLICY AT BANK BRI GADANG UNIT MALANG CITY - Sri Rahayu; Imam Mukhlis (International Journal Labs, 2022)
This study aims to examine the effect of perceptions of provisions, perceptions of usefulness and perceptions of risk of credit restructuring policies on customer decisions of Bank BRI Gadang Unit Malang City. This study uses primary data obtained from questionnaires distributed to customers of Bank BRI Gadang Unit Malang City. In this study using a quantitative approach with 33 respondents. In this study using multiple linear regression analysis method with other tests such as classical assumption test, validity test and reliability test with data processing using SPSS software. The results of this study indicate that there are 2 independent variables that have a significant effect on the dependent variable of customer decisions. 2 independent variables that have a significant effect, namely the perceived benefit variable and the variable perceived risk of credit restructuring. Then the validity test, reliability test and classical assumption test were declared feasible to be used for this research.